Leaf area and stomatal density of Rhizophora mucronata Poir. under high and low light environment of Nature Tourism Park Angke-Kapuk, Jakarta, Indonesia - Bagus Tito Wibisono; Tri Wahyuni; Murniati Simanjuntak; Abizar; Supriyatin (Bioma, 2024)
Each type of mangrove has specific stomatal characteristics, one of which is stomatal density. This stomatal density is directly proportional to the rate of evaporation, transpiration, and photosynthesis which is a form of mangrove adaptation to its environment. One of the external factors affecting stomatal density is light intensity which can vary due to canopy cover. This study aims to compare the stomatal density of Rhizophora mucronata Poir. in the Angke-Kapuk area, Jakarta, Indonesia. The location is a mangrove conservation area that has experienced a lot of environmental pressure, especially due to population growth and land conversion into settlements. Descriptive methods was used with transect sampling techniques at locations that represent very open and very closed canopies determined by purposive sampling. Stomatal sampling was carried out by applying a transparent nail polish on the lower surface of the leaf and then covering it with tape. The tape was observed using a microscope, and showed that Rhizophora mucronata Poir. has a low stomatal density. The results of the parametric independent sample t-test showed that the stomatal density of Rhizophora mucronata was not significantly different between very open and very closed canopy cover.